Intraoperative radiofrequency ablation for unresectable abdominal paraganglioma: a case report - Magalhaes, Isabelle P. A.; Boger, Bibiana D.; Gomes, Nathalia L.; Martins, Guilherme L. P.; Bomfim, Leomarques A.; Fagundes, Gustavo F. C.; Rocha, Roberta S.; Coelho, Fernando M. A.; Chambo, Jose L.; Latronico, Ana Claudia; Fragoso, Maria Candida B. V.; Hoff, Ana O.; et al. (Frontiers in Endocrinology, 2024)
For pheochromocytoma and paraganglioma (PPGL), the efficacy of percutaneous ablative therapies in achieving control of metastatic tumors measuring <3 cm had been demonstrated in only few reports, and intraoperative radiofrequency ablation (RFA) of locally invasive primary PPGLs has not been reported. We presented the case of a 31year-old man who had a 9-cm functioning unresectable PPGL. He was treated with 13 cycles of cytotoxic chemotherapy without objective tumor response, according to the Response Evaluation Criteria in Solid Tumors (RECIST). Subsequently, magnetic resonance imaging revealed a 9.0 × 8.6 × 6.0-cm retroperitoneal mass that extended to the inferior portion of the inferior vena cava, the inferior mesenteric artery, and the infrarenal aorta. Biochemical evaluation demonstrated high level of plasma normetanephrine (20.2 nmol/L, normal range <0.9 nmol/L). Genetic investigation showed the germline pathogenic variant c.1591delC (p. Ser198Alafs*22) in the SDHB gene. I 131 -metaiodobenzylguanidine scintigraphy was negative and Ga 68 -dotatate PET-CT scan showed high tumor uptake without distant metastases. On open laparotomy, tumor debulking was not possible. Therefore, intraoperative RFA was performed by a highly experienced team of interventional radiologists. At 12 months after the RFA, the tumor volume decreased from 208 to 45 mL (78%), plasma normetanephrine decreased from 20.2 to 2.6 nmol/L (87%), and the doxazosin dose was reduced from 16 to 8 mg/day.To our best knowledge, this was the first report on intraoperative RFA that markedly reduced the size of a large primary unresectable PPGL, along with clinical and biochemical responses.